Analysis of some Topological Indices in the Molecular and Line Graph of Bismuth Tri-iodide[m, n] by M-polynomial Approach - Babaei, Azizollah; Cherati, AllahBakhsh Yazdani; Yousefpour, Rohollah (Discontinuity, Nonlinearity, and Complexity, 2026)
Mathematics has many applications in other sciences, especially in chemistry, where the theory of chemical graphs is one of the most important uses. Analyzing the properties dependent on the structure of different molecules is of significant importance. One of these molecules, whose structure is investigated in this article, is Bismuth tri-iodide [m, n]. In this article, we investigate the relations between the first δ- Gourava index, second δ- Gourava index, SK Revan index, SK1 Revan index, and SK2 Revan index via M-polynomials. These indices are then calculated for the molecular graph and the line graph of Bismuth tri-iodide [m, n], and the results are presented.